ANALISIS HUBUNGAN PERSEPSI PASIEN TENTANG MUTU PELAYANAN KESEHATAN DENGAN TINGKAT KEPUASAN PASIEN DI PUSKESMAS PENUMPING KOTA SURAKARTA - Hufron, Agus; Supratman, Supratman (Jurnal Berita Ilmu Keperawatan, 2008)
Health Service Center is one of the health service of society that have fundamental duty to give construction of health of elementary health service and society. Result of Quality Assurance Penumping Health Service Center survey team to the patients that visit in the early year of 2006 shown result that 3% patients express dissatisfy, 21% patient less satisfy, 49% patients enough satisfy and 17% expressing satisfy. To analyse the relation between the patient’s perception about the quality of health service with story level of satisfaction patient in Penumping Health Service Center of Surakarta City, done by research with descriptive correlation method of the data is taken by giving kuesioner to 111 patients / families that are use the health service in Penumping Health Service Center with random sampling, the data is processed and also analysed with logistic research. The Result of regresi shown that 1). 37,8 % patients express the quality of service is still lower, and 39,6% expressing satisfaction of patients is still lower. 2). According to the statistical test, prove that there are relation which are positive and signifikan between the quality of health service with satisfaction of the patients in Penumping Health Service Center of Surakarta City. 3). Based on the result of multi variant test in the reality of variable sub quality of the health service in Penumping Health Service Center by giving constribution to get equal to 59,9 % to satisfaction of the patients. Health Service Center suggested to increase its discipline and to join the employees to the training program according to its profession.